2013
DOI: 10.1002/ase.1373
|View full text |Cite
|
Sign up to set email alerts
|

An enriched multimedia eBook application to facilitate learning of anatomy

Abstract: This pilot study compared the use of an enriched multimedia eBook with traditional methods for teaching the gross anatomy of the heart and great vessels. Seventy-one first-year students from an Australian medical school participated in the study. Students' abilities were examined by pretest, intervention, and post-test measurements. Perceptions and attitudes toward eBook technology were examined by survey questions. Results indicated a strongly positive user experience coupled with increased marks; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 41 publications
4
50
0
4
Order By: Relevance
“…The results of the present study are consistent with those of the study by Sandars et al in which they showed that digital storytelling could increase the involvement of first year medical students with content, and consequently having a positive effect on their learning (29). Suwardy et al and Shelton et al also reported the positive impact of storytelling (22,24). The results of the present study were consistent with those of the study by Paulins et al who reported the positive effect of enriched presentations (9).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are consistent with those of the study by Sandars et al in which they showed that digital storytelling could increase the involvement of first year medical students with content, and consequently having a positive effect on their learning (29). Suwardy et al and Shelton et al also reported the positive impact of storytelling (22,24). The results of the present study were consistent with those of the study by Paulins et al who reported the positive effect of enriched presentations (9).…”
Section: Discussionsupporting
confidence: 92%
“…These modern technologies offer improved learning affordances [27], are supported through mobile mixed reality delivery, and allow health and medical students improved experiential learning [2,17,18]. Although not of the highest visual fidelity, these mobile platforms still enable the core tenants of enhanced learning outcomes [35], reduction of cognitive load [34], and "functional task alignment" [38] (p. 387) by focusing on the pedagogy and human functional factors of content, task, learning stage, ability, capabilities, task difficulty, and instructional features to transfer learning [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, modern technology can allow this, and provide health students with learning modules that are far more experiential that other modes [2,17,18] and learning that can be beneficially self-directed [3]. New multimedia knowledge can be updated instantly within an application, and important concepts presented to the student that can assist their understanding of overall concepts [4].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Good teaching effect has been achieved. Stirling et al [4] made a comparison of the use of an enriched multimedia eBook with traditional methods for teaching the gross anatomy of the heart and great vessels. The results show that as initial interaction with the multimedia content together with active experimentation in the anatomy lab was conducted, students were found to get improved in the final test.…”
Section: State Of the Artmentioning
confidence: 99%